Interface Characteristics and Mechanical Properties of 2024 Aluminum Alloy and 304 Stainless Steel Dissimilar Alloys FSLW Joint with Ni Interlayer - Jun Liu; Ruixiu Guo; Peng Gong; Yumei Yue; Zhanxing Yu; Yewei Zhang (Metals, 2022)
The composite structure of aluminum and steel (Al/steel) dissimilar metals has been applied in manufacturing industries for lightweight products, and friction stir lap welding (FSLW) has advantages for the welding of these two metals. To further enhance the strength of the Al/steel FSLW joint, a 0.02 mm thick nickel (Ni) foil was chosen as the interlayer, and slight plunging depth of a tool pin into the lower steel sheet was designed, which can respectively change the intermetallic compounds (IMCs) type and produce small welding heat. Choosing dissimilar 2024 aluminum alloy and 304 stainless steel materials as the research subject, the characteristics of the lap interface and the mechanical properties of the joint were mainly discussed. The results showed that the lap interface between the upper aluminum and lower steel sheets was made up of an AlNi3 IMCs layer, hook structure and mechanical occlusion. The AlNi3 IMCs layer with 2 μm thickness was in a reasonable range positive to the joint strength. When the rotating speed of the stirring tool increased from 800 to 1200 rpm and the welding speed of 75 mm/min was constant, the hook structure and the mechanical occlusion were both enhanced, and the tensile shear strength of the joint was decreased. A maximum joint tensile shear strength of 217 MPa was obtained at 800 rpm, and the strength value was 47.2 percent of that of the 2024 aluminum alloy base material. The Al/steel joint with shear fracture mode presented a brittle–ductile mixed fracture.